A Hirschsprung disease locus at 22q11?. Issue 3 (1st March 1999) - Kerstjens-Frederikse, W S; Hofstra, R M W; van Essen, A J; Meijers, J H C; Buys, C H C M
Abstract : We report a boy with truncus arteriosus, dysmorphic features, developmental delay, passing hypotonia, short segment Hirschsprung disease (HSCR), and paroxysmal hypoventilation. FISH analysis showed an interstitial deletion in chromosome band 22q11.2 coinciding with the deletions found in DiGeorge syndrome and velocardiofacial syndrome. Mutation scanning of RET, GDNF, EDNRB, and EDN3, genes associated with Hirschsprung disease, showed no aberrations. Since we know of two more patients with velocardiofacial syndrome and HSCR, we hypothesise that a gene responsible for proper development of the enteric nervous system may be included in the 22q11.2 region.